Slovak Verbal Derivatives in Background Taxis Constructions - OVCHINNIKOVA, IRINA GERMANOVNA (SlavVaria, 2021)
Slovak Verbal Derivatives in Background Taxis Construction. Taxis semantics expresses simultaneity, precedence and posteriority of events in the time span span. Taxis construction contains two propositions in the sentence. Background taxis usually appears in complex sentence s with circumstantial clause clauses, where taxis semantics plays a sub -dominant role role. A verbal derivative , which inherits tense and aspect semantic components from its original verb form, is able to participate in background taxis constructionconstructions. Semantic peculiarities of the verb predict its involvement in the taxis constructionconstruction. The objective of this paper is to clarify how verbal derivatives function in background taxis constructions in Slovak Slovak.